Social Transformation in AI-Driven Digital Ta’aruf: An Islamic Family Law Analysis of the Muzz Application - Mufatihatuttaubah Rorom Ika Putri (Pustaka Peradaban, 2026)
The development of digital technology, especially artificial intelligence, has triggered significant social changes, including in the mechanism of ta'aruf which can now be carried out online through special platforms. This article analyzes the Islamic family law response to the transformation of AI-based ta’aruf practices, focusing on the Muzz app as a representation of a modern introductory platform. This research uses a literature study method that examines the literature on Islamic family law, digital technology, and AI. The findings of the study indicate that the application of sharia values, especially maqasid al-shari’ah, is a crucial foundation in the development of safe and ethical digital ta’aruf practices, as well as being adaptable to various other digital ta’aruf platforms. In this context, hifz al-‘ird encourages strong identity verification to prevent data manipulation; Hifz al-Din demands good communication manners and seriousness of intention; while Hifz al-Nafs requires protection from the risk of cybercrime through adequate data security. AI technology can strengthen these mechanisms through AI-based identity verification, behavioral anomaly detection, and automated moderation. The implications of this study confirm the need for fiqh guidelines for online interaction, sharia standards for the nadhar mechanism and guardian involvement, application certification according to sharia principles, and pre-marital data protection regulations. Perkembangan teknologi digital, khususnya kecerdasan buatan (AI), telah memicu perubahan sosial yang signifikan, termasuk dalam mekanisme ta'aruf yang kini dapat dilakukan secara daring melalui platform khusus. Artikel ini menganalisis respons hukum keluarga Islam terhadap transformasi praktik ta'aruf berbasis AI, dengan fokus pada aplikasi Muzz sebagai representasi platform perkenalan modern. Penelitian ini menggunakan metode studi pustaka yang mengkaji literatur tentang hukum keluarga Islam, teknologi digital, dan AI. Temuan studi menunjukkan bahwa penerapan nilai-nilai syariah, khususnya maqasid al-shari’ah, merupakan fondasi krusial dalam pengembangan praktik ta'aruf digital yang aman dan etis, serta dapat diadaptasikan ke berbagai platform ta'aruf digital lainnya. Dalam konteks ini, hifz al-‘ird mendorong verifikasi identitas yang kuat untuk mencegah manipulasi data; hifz al-din menuntut tata krama komunikasi yang baik dan keseriusan niat; sementara hifz al-nafs memerlukan perlindungan dari risiko kejahatan siber melalui keamanan data yang memadai. Teknologi AI dapat memperkuat mekanisme ini melalui verifikasi identitas berbasis AI, deteksi anomali perilaku, dan moderasi otomatis. Implikasi dari studi ini mengonfirmasi perlunya pedoman fikih untuk interaksi daring, standar syariah untuk mekanisme nadhar dan keterlibatan wali, sertifikasi aplikasi sesuai prinsip syariah, serta regulasi perlindungan data pra-nikah.